PEMANFAATAN MEDIA DIGITAL INSTAGRAM DALAM PEMASARAN DI KA-GA-NGA COFFEE MAKASSAR - Rizqi Salsabila , Ayu; Zelfia, Zelfia (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This thesis discusses the Utilization of Instagram Digital Media in Marketing at Ka-Ga-Nga Coffee Makassar. The main issue is whether Instagram's Digital Media has an effect on marketing at Ka-Ga-Nga Coffee. The type of research used is descriptive analysis, where the data is in qualitative form obtained from interviews and observations. This research lasted for one month located at Ka-Ga-Nga Coffee Jalan Bougenvile no 23, Makassar. The theory used in this study is Uses and Gratification, which focuses on how the media meets the personal and social needs of audiences. The results of this study indicate that the Instagram account @kagangacoffee has been actively marketing through Instagram Digital Media by pressing on brand identity as a Makassar children's coffee shop.